Effect of Crop Insurance and Employment Support on Agricultural Households’ Well-being: Evidence from India (Indian Journal of Extension Education, 2025)
Indian farmers jointly follow farm risk management and livelihood diversification to augment their income for better well-being. The uncertainties in climatic conditions and rural employment market pose dangers of income insecurity to already low-incomed farmers. Crop insurance is a promising production risk management technique, which, through Pradhan Mantri Fasal Bima Yojana (PMFBY), seems beneficial in improving Indian farmers’ well-being by ensuring financial support during crop loss. Similarly, Mahatma Gandhi National Rural Employment Guarantee Scheme (MNREGS) provide income security by ensuring guaranteed regular employment. This paper strives to contribute to the knowledge related to PMFBY and MNREGS. The Binary Logit Regression results suggest that marginal and small farmers are less involved in both whereas socially marginalized farmers participate more in MNREGS but less in PMFBY. The possession of education, agricultural training and crop loss experience enhance their participation in both. Further, the Propensity Score Matching (PSM) results of all the three different matching methods suggest the positive impact of PMFBY and MNREGS on household usual consumption expenditure. The study suggests to enhance crop insurance adoption by boosting education, agricultural training, and membership in farmer organization. Further, ensuring diverse livelihood opportunities to farmers for their improved well-being.